THE HUMAN RIGHTS PROTECTION IN THE ECONOMIC AFFAIRS OF INDONESIA - Siti Rodhiyah Dwi Istinah; Sri Kusriyah; Rakhmat Bowo Suharto (UNISSULA, 2021)
The purpose of this study is to analyze and explain the protection of human rights in the economic sector for citizens to be able to enjoy a socially just economic development as well as to analyze and explain the challenges and obstacles in protecting human rights in the economic sector in an effort to realize social justice in the Constitution 1945. important in the constitution which gave birth to the concept of protecting human rights in the economic sector, which was initiated by the founding fathers, regarding Indonesian socialism. Hatta's idea was in line with Soekarno's thinking as